Potentially toxic elements in human scalp hair around China’s largest polymetallic rare earth ore mining and smelting area - Lijun Dai; Li Deng; Weili Wang; You Li; Lingqing Wang; Tao Liang; Xiaoyong Liao; Jinwoo Cho; Christian Sonne; Su Shiung Lam; Jörg Rinklebe (Environment International, 2023)
There is a growing concern about human health of residents living in areas where mining and smelting occur. In order to understand the exposure to the potentially toxic elements (PTEs), we here identify and examine the cadmium (Cd), chromium (Cr), copper (Cu), manganese (Mn), nickel (Ni), lead (Pb) and zinc (Zn) in scalp hair of residents living in the mining area (Bayan Obo, n = 76), smelting area (Baotou, n = 57) and a reference area (Hohhot, n = 61). In total, 194 hair samples were collected from the volunteers (men = 87, women = 107) aged 5–77 years old in the three areas. Comparing median PTEs levels between the young and adults, Ni levels were significantly higher in adults living in the smelting area while Cr was highest in adults from the mining area, no significant difference was found for any of the elements in the reference area. From the linear regression model, no significant relationship between PTEs concentration, log10(PTEs), and age was found. The concentrations of Ni, Cd, and Pb in hair were significantly lower in the reference area when compared to both mining and smelting areas. In addition, Cu was significantly higher in the mining area when compared to the smelting area. Factor analysis (FA) indicated that men and women from the smelting area (Baotou) and mining area (Bayan Obo), respectively, had different underlying communality of log10(PTEs), suggesting different sources of these PTEs. Multiple factor analysis quantilized the importance of gender and location when combined with PTEs levels in human hair. The results of this study indicate that people living in mining and/or smelting areas have significantly higher PTEs (Cu, Ni, Cd, and Pb) hair levels compared to reference areas, which may cause adverse health effects. Remediation should therefore be implemented to improve the health of local residents in the mining and smelting areas.